MBKM-Based Curriculum Development in the Islamic Religious Education Study Program - Hayati, Dina Nur; Manggali, Cahya Arrum (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Indonesian universities are currently adopting the concept of free learning, independent campus to strengthen student independence in the learning process. This research aims to analyze the implementation of the idea of free learning on an independent campus in the context of the Islamic religious education study program. Research method This research was carried out using the literature study method, which studied various relevant literature sources. The research results show that the application of the independent campus learning concept in Islamic religious education courses involves multiple aspects such as the curriculum, MBKM policy, the position of MBKM in the context of curriculum development, the forms of MBKM, the design of its implementation, and providing examples of the implementation of MBKM itself. Students are instructed to play an active role in the learning process, create a learning portfolio, and develop independent skills. These results illustrate the extent to which these concepts can be integrated into an Islamic context, enabling students to increase their religious understanding and relevant practical skills. This study shows that curriculum plans and learning strategies need to be adjusted again to ensure that the concept of an independent learning campus can support student capacity development in the field of Islamic religious education. We hope that this research will contribute to a better understanding of the application of these concepts in the specific context of this research program and provide a basis for further refinement and development in the future.